Doble imposición del IGV en importación y utilización de servicios: ¿problema de interpretación o de regulación? - Assereto Bossio, Juan José (2016)
This article addresses the discussion about the validity in the interpretation of the double impact of “VAT” on a single economic event by setting two different taxable events. Likewise, it is explained if this interpretation infringed the systematic of tax and violates constitutional principles taxation such as equality and non-confiscatory.